A TRIO IN BALANCE: BIODIVERSITY-HEALTH-DISEASE - Pacheco Figueroa, Coral Jazvel; Valdez Leal, Juan de Dios; Mata Zayas, Ena Edith; Gama Campillo, Lilia María; Moguel Ordoñez, Eduardo Javier (Kuxulkab', 2020)
Biodiversity and the health-disease binomial have a triangular relationship. The human being is ending the stability of this triangle, which maintains life as we know it; due to the increase in population and its activities that modify ecosystems to satisfy the growing demands for food, fresh water, fiber, wood and fuel, among other needs. Consequently, changes in land use, fragmentation and loss of habitat, which favor contact between people, domestic and wild animals; which increases the risk in the transmission of infectious diseases, both emerging and reemerging. The maintenance of biodiversity represents a potential solution in the presence of diseases, because it allows the regulation and damping of them. The lack of control of these diseases leads to large pandemics, which are also zoonotic. Among them the black plague, leptospirosis, dengue, Ebola, chikungunya, COVID-19 and even the common flu. All these diseases have a common factor, which is the alteration of the habitat or environmental condition caused by anthropic causes.
Keywords: Zoonosis; Pandemic; Emergent; Triad; Ecosystemic services